Reflections of kinesiology practicum students in an adult fitness program - Chen, Yu Chun; Reeves, Connie Smiley (Journal of Health and Physical Literacy, 2025)
Although many individuals with a physical education teacher education degree seek employment in teaching K-12 physical education, the settings for their skillset are limitless and working with the senior adult population is one of them. The purpose of this research was to examine the expectations and experiences of kinesiology undergraduate students on learning how to teach senior adults in exercise classes during the practicum. Kinesiology majors enroll in a practical field experience before they graduate. They work with senior adults, ages 55+, enrolled in fitness classes at the university. A primary instructor and practicum students teach classes. Students learn to lead exercise classes, create playlists, classroom management, and communication skills. A total of 50 students were enrolled in the practicum during the 2021-22 academic year. Before the practicum, students were instructed to “provide discussion about expectations for the class. After the practicum, students were asked to “provide a reflection of experiences. Did beliefs about working with senior adults change because of the experience? On a scale of 1 to 10, with 10 being the highest, what was your level of comfort working with senior adults? The standard interpretive methods of analytic induction and constant comparison were used to analyze the data. Before the practicum, participants expressed fear of member injuries, fear of being criticized, as well as not knowing how to teach a class and communicate with older adults. After the experience, the participants felt acceptance by members, gained confidence in teaching, and developed positive relationships. The average comfort level rating in working with senior adults increased from 6.4 to 9.3 during the two timepoints. The opportunity for PETE/Kinesiology students to work with senior adult populations could help them gain marketable experiences and provide professional leadership in their community.